Training and Mentoring of Classroom Action Research as a Strategy for Developing Chinese Teacher Skills - Hermanto Hermanto; Muhammad Abdul Ghofur; Puspita Sari Sukardani; Binar Kurnia Prahani; Hanandita Veda Saphira (Universitas Lambung Mangkurat, 2024)
This proposed community service activity offers a solution in the form of training activities to increase teacher skills and competence. The intended training is for training and mentoring scientific work; the easiest is classroom action research (CAR). This is taken with the consideration that, besides being easy, it is also based on the real experience that Chinese teachers have gained in Surabaya. The implementation method to solve this problem is divided into three stages, namely the preparation stage, the implementation of training and mentoring, and post-training and mentoring. The results of the mentoring stated that participants considered this material in accordance with their practical needs as Chinese teachers and could adapt it to the conditions of their respective schools. Overall, the training was successful in creating a positive and meaningful experience for participants, illustrating the effectiveness and responsiveness of UNESA's Confucius Institute in meeting the needs of trainees.